Susceptibility of four different honey bee species to Nosema ceranae - Chaimanee V. (2014)
In this study, we investigated the infectivity of Nosema ceranae and the immune response of the European honey bee, Apis mellifera and the Asian honey bee species, Apis cerana, Apis dorsata and Apis florea when inoculated with two isolates of N. ceranae isolated from different climates (Canada and Thailand), using cage experiments. The results indicated that the local isolate of N. ceranae (Thailand) had high infectivity in A. mellifera, A. cerana and A. dorsata but only a few spores were observed in A. florea. However, we found that only two honey bee species, A. mellifera and A. dorsata became infected when inoculated with N. ceranae isolated from Canada. Finally, our results showed that transcript levels of antimicrobial peptides (AMPs) in Asian honey bees were significantly higher than that of A. mellifera in both the control and N. ceranae inoculated bee groups. Comparing the expression of AMPs between the control and inoculated bees in each species, it was evident that N. ceranae inoculations did not affect the expression level of abaecin in all four honey bees species investigated in this experiment. Nevertheless, we found a significant up-regulation of apidaecin in A. cerana and A. florea when inoculated with N. ceranae (Canadian isolate). Also, the mRNA levels of hymenoptaecin were significantly increased in A. cerana after inoculation by N. ceranae isolated from Canada as compared with the Thai isolate. © 2012 Elsevier B.V.